Sunrise - Warren, Susan May, 1966- (Sky King ranch, 2022)
"A decade after leaving his family's bush pilot operation to become a Pararescue Jumper, Dodge Kingston is back home in Alaska. He hadn't counted on meeting up again with Echo, a girl with a spirit as free as the sky. When she goes missing, he hopes all her skills will keep her safe until he can reach her-and that she'll accept his help when he does"--